2005
DOI: 10.1038/labinvest.3700315
|View full text |Cite
|
Sign up to set email alerts
|

Impaired nonhomologous end-joining in mismatch repair-deficient colon carcinomas

Abstract: Frameshift mutations of coding mononucleotide repeat of the hRAD50 gene and formation of the mutant hMRE11 splicing variant are frequent events in tumors with mismatch repair (MMR) deficiency. Both the hRAD50 and hMRE11 proteins form a heterotrimer with the NBS1, and this heterotrimer is involved in the double strand DNA break repair by homologous recombination and nonhomologous end-joining (NHEJ). In order to clarify the role of hRAD50 and hMRE11 gene alterations in MMR-deficient tumors, we analyzed the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…One of the questions that still remains partially unanswered is the exact mechanism why MSI-H cells are more sensitive to camptothecins than MSS cells. Several studies have demonstrated that deficiency in the MMR genes leads to secondary mutations in microsatellite tracts as those present in the monucleotide repeats regions of the principal caretaker genes implicated in the repair of DSB, such as the Mre11/Nbs1/Rad50 protein complex (Giannini et al, 2004;Koh et al, 2005). These observations have been extended to tumour series from sporadic and familial MSI-H CRC cases (Miquel et al, 2007).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…One of the questions that still remains partially unanswered is the exact mechanism why MSI-H cells are more sensitive to camptothecins than MSS cells. Several studies have demonstrated that deficiency in the MMR genes leads to secondary mutations in microsatellite tracts as those present in the monucleotide repeats regions of the principal caretaker genes implicated in the repair of DSB, such as the Mre11/Nbs1/Rad50 protein complex (Giannini et al, 2004;Koh et al, 2005). These observations have been extended to tumour series from sporadic and familial MSI-H CRC cases (Miquel et al, 2007).…”
Section: Discussionmentioning
confidence: 77%
“…We have suggested that cell lines harbouring mutations in both MRE11 and RAD50 were the most sensitive to CPT-11. Previous reports showed that mutations in these genes are also associated with increased response to g-irradiation, another type of DNA-damaging agent causing DSB (Koh et al, 2005). In addition, the preferential cytotoxic effect showed by another DNA-damaging agent, Bleomycin, in MSI-H cell lines might be explained by the same genetic defect (Li et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The MMR system has also been implicated in S-phase checkpoint control in response to low doses of IR (62,63). MMRdeficient CRC tumors and cell lines tend to accumulate mutations within microsatellite repeats of genes implicated in the doublestrand break (DSB) repair pathway (e.g., MRE11 and RAD50) (64,65). Furthermore, impaired MMR function results in inactivation of ATM and MRE11 genes, which correlates with impairment of the DSB repair system in leukemia and lymphoma cell lines (66).…”
Section: Discussionmentioning
confidence: 99%
“…PMS2 mutations associated with Turcot syndrome are known to compromise the DNA MMR. Moreover, experimental studies indicate that the repair of DSBs is frequently impaired in MMR-deficient cells, leading to slightly increased radiosensitivity (42,43). This may explain our finding of slightly impaired DSB repair capacity in the patient AITB, whereas the aberrant DSB repair may be an additional mechanism contributing to genomic instability and tumorigenesis.…”
Section: Discussionmentioning
confidence: 44%